MODERASI BERAGAMA KONTEMPORER (STUDI TAFSIR TEMATIK) - M. Khoirul Muzakki; Ana Maulidya Rohmatul Maula (LPPM Universitas Uluwiyah Mojokerto, 2025)
This study examines the Qur’anic perspective on interreligious relations in the contemporary world, emphasizing the relevance of its principles in addressing modern pluralistic societies. Islam, as a divinely revealed religion, acknowledges the existence of other religions while maintaining the theological conviction that Islam is the religion approved by God. The Qur’an recognizes religious diversity as part of divine will and explicitly rejects coercion in matters of faith. Employing a thematic interpretation approach (tafsir maudhui), this study systematically collects and analyzes Qur’anic verses related to interreligious relations. The findings reveal that the Qur’an promotes principles such as tolerance, justice, peace, equality, and consultation as foundations for ethical coexistence with non-Muslims, while preserving doctrinal exclusivity in matters of belief (aqidah).